Determinants of Healthcare Profitability: The Role of Financial and Operational Leverage in Indonesia - Indri Ayu Tansar; Gilang Sekar Tadjie; Siti Amiah (P3M, STIE Pasundan, Bandung, Indonesia., 2026)
This study investigates the influence of Operating Leverage (Degree of Operating Leverage/DOL) and Financial Leverage (Degree of Financial Leverage/DFL) on the profitability of healthcare sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. Profitability in this study is measured using Net Profit Margin (NPM), a metric that reflects operational efficiency relative to net sales and is directly influenced by a company’s leverage structure. The novelty of this research lies in its focus on the post-COVID-19 period, its exclusive examination of the healthcare sector — which has unique operational cost structures and strict regulatory environments — and its use of NPM as the profitability proxy, which is less commonly employed compared to ROA or ROE in similar studies. A quantitative approach with a verificative and explanatory survey method was adopted. The sample consisted of 12 healthcare companies selected through purposive sampling, yielding 36 total observations across three years. Data were sourced from official IDX financial reports and analyzed using multiple linear regression with the assistance of SPSS software. Prior to regression analysis, classical assumption tests — including normality, multicollinearity, autocorrelation, and heteroscedasticity — were conducted, and all assumptions were satisfied. The descriptive statistics revealed that DOL had a negative mean (–14.72) with a large standard deviation (44.93), indicating high operational risk and significant variation among companies. DFL showed a positive mean (0.619), suggesting moderate debt utilization, while NPM averaged 34.71%, reflecting a relatively healthy net profit capacity. The results of the partial t-tests showed that DOL (t = 1.407; sig. = 0.169) and DFL (t = 0.740; sig. = 0.465) did not have a significant individual effect on NPM. The simultaneous F-test also indicated no significant joint effect (F = 1.404; sig. = 0.260). The Adjusted R² value of 0.809, however, suggests that the model explains approximately 80.9% of the variation in NPM, with the remaining 19.1% attributable to other factors not captured in the model. These findings indicate that neither operating leverage nor financial leverage serves as a primary determinant of profitability in the healthcare sector. Instead, factors such as operational efficiency, healthcare service demand, government regulation, sales growth, and macroeconomic conditions are considered more dominant in shaping financial performance. Future research is recommended to incorporate additional variables — such as liquidity ratios, asset efficiency indicators, and macroeconomic variables — to gain a more comprehensive understanding of profitability dynamics in this sector.